Freeze-Drying and Subsequent Storage of Fixed Pasteur Strain Rabies Virus - Varianytsia, Viktoriia V.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):162.